ANALISIS KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DESA SINDANGSARI KECAMATAN CISOMPET KABUPATEN GARUT - Purnawan, Ade; Karmila, Mila; Nurbudiwati; Sutiana, Jajang (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The village government's lack of socialization regarding the population administration process to the community and suboptimal infrastructure can disrupt the quality of services. The aim of this research is to determine the quality of administrative services as well as supporting and inhibiting factors at the Sindangsari Village Office, Cisompet District, Garut Regency. The research method used is qualitative research, data collection techniques: observation, interviews and documentation. The research results show that the quality of Service Quality from the aspects: 1. Tangible with indicators of employee appearance and comfort of the place where Service Quality is carried out and the interview results obtained have not run optimally, dimension 2. Reliability with indicators of employee accuracy and employee ability and interview results it was found that this had been implemented well, 3. Responsiveness with indicators Responding to every service user and employee providing Service Quality quickly and from the interview results obtained this had been implemented well 4. Assurance with indicators Officers provided guarantees on time and officers provided cost guarantees and the results of the interviews obtained have been implemented well. 5. Emphaty with the indicator Prioritizing the interests of service users and employees serving non-discriminatorily and this has not been implemented well. Inhibiting factors still have negative perceptions from the community regarding service quality, supporting factors include namely so that employees can provide better service quality with the enthusiasm of each employee. From the research results obtained in the field, it is in accordance with what was stated by the informants to find out the analysis of the quality of Population Administration Services in Sindangsari Village, Cisompet District, Garut Regency using 5 variables as reference material and these five variables have been implemented quite well in Sindangsari Village, Cisompet District. Garut Regency.